Dokumentacja techniczna miasta Bydgoszczy (Kronika Bydgoska, 2020)
The article presents technical documentation of the city of Bydgoszcz, which is stored in the State Archives of Bydgoszcz. The author focused primarily on documentation from the archival group Records of the City of Bydgoszcz. They contain blueprints of the most important buildings in the city, private enterprises, and municipal companies. An analysis was made in accordance with archival references of the group. It should be emphasized that technical documentation is an important archival source for studies on the history of the city. The article has been written for the purposes of popularization.